PERAN MAHASISWA KAMPUS MENGAJAR UNTUK PENINGKATAN LITERASI NUMERASI SISWA - Kurniasari, Septiana; Yunus, Muhammad; Nuralim, Sandi; Mantulangi, Tirani; Alfan Habibi, Moh Arif (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2023)
The low level of numeracy literacy in Indonesia causes human resources to be uncompetitive. To solve these problems, through the Kampus Mengajar Program Batch 5, students develop programs that are implemented during their assignment at SD Negeri 12 Kabila. The purpose of this activity is to find out the role of Kampus Mengajar students Batch 5 in increasing students' numeracy literacy. The method used in this activity is descriptive method. The results of the activity show that the Kampus Mengajar Program Batch 5 is very influential in realizing an increase in numeracy literacy in students. Students as agents of change also play an important role in increasing enthusiasm, learning motivation and student learning outcomes as well as creating fun and enjoyable learning media.